First-, second- and third-line lung cancer treatment patterns and associated costs in a US healthcare claims database. (July 2015) - Ramsey, Scott; Henk, Henry J; Smith, Gregory L; Sollano, Josephine; Chen, Connie
Aim: To identify the most common first, second, and third lines of therapy and associated costs among patients treated for lung cancer.Methods: This retrospective analysis of healthcare claims identified patients treated for lung cancer from January 2007 through April 2012. Patients were enrolled in first-, second-, or third-line therapy cohorts and stratified by the number of discrete treatments received or by the specific chemotherapy or biologically targeted agent or combination of agents.Results: Of patients receiving first-line treatment (either chemotherapy or biologically targeted therapies), 18.3% and 4.4% received second-line and third-line treatment, respectively. Pemetrexed, topotecan, docetaxel, and erlotinib were the most commonly second-line regimens; pemetrexed and erlotinib were the most common third-line regimens. While total costs increased with increasing lines of treatment, costs per patient per month remained stable or decreased overall.Conclusion: Platinum/taxane combined treatment is still the mainstay of first-line therapy for lung cancer treatment for those with advanced disease. Second- and third-line therapy is still prescribed infrequently, although newer agents are more commonly used in this setting.